Enfrentamientos entre grupos de poder por el dominio del Cabildo de Quito entre 1735 y 1739 - Ramos Gómez, Luis (Revista Complutense de Historia de América, 2006)
We analyse the confrontations between diverse power groups in the city Council of Quito, as well as the mechanisms put in march by the local or provincial government to protect its coreligionists and to eliminate the rivals.